MiR-495-3p regulates cell migration and invasion in papillary thyroid carcinoma - Alves, Letícia Ferreira; Geraldo, Murilo Vieira (Frontiers in Oncology, 2023)
Papillary thyroid carcinoma (PTC) is the most prevalent histotype of thyroid cancer and the presence of BRAFV600E mutation in these tumors is related to the malignancy and prognosis of the disease. In recent years attention has been focused on the role of microRNAs in the biology of PTC cells, especially in their role in the modulation of pathways related to tumorigenesis. DLK1-DIO3-derived miRNAs have been shown to play important roles in tumor context and are globally downregulated in PTC. Based on a previous in silico target prediction and gene enrichment analysis, we identified miR-495-3p as the candidate with the highest tumor suppressor potential role in PTC among DLK1-DIO3-derived miRNAs. We used bioinformatics and an in vitro model of miR-495-3p overexpression to further understand the influence of this molecule on the tumorigenic processes of PTC. Overexpression of miR-495-3p impaired cell migration and invasion of PTC cells harboring the BRAFV600E mutation and affected the expression of targets predicted in the bioinformatic analysis, such as TGFB2, EREG and CCND1. Overall, our results indicate that the loss of miR-495-3p expression during PTC development might play an important role in its progression.